Implementation of Smart Home Automation System Using Internet of Things Technology - Berliana Setyaningrum; Ahmad Lutfi Abdillah; Mila Makhfiroh Sufrotul Laili (Proceeding of the International Conferences on Engineering Sciences, 2025)
The advancement of Internet of Things (IoT) technology has significantly transformed traditional homes into intelligent living environments. This study presents the implementation of a smart home automation system utilizing IoT components to control and monitor household devices remotely. The system integrates NodeMCU ESP8266 microcontrollers, sensors (temperature, motion, light), and actuators (relays for lights, fans, and appliances) which are connected through a Wi-Fi network. A mobile application is developed to enable real-time control and monitoring, enhancing user convenience, energy efficiency, and home security. The system also includes automated scenarios such as turning off lights when no motion is detected or adjusting ventilation based on temperature. Testing results show that the system responds within an average delay of less than 1.5 seconds and maintains stable performance across various network conditions. The findings confirm that IoT-based home automation offers a scalable, cost-effective solution to improve the quality of life and resource management. This study contributes to the development of sustainable and intelligent home systems for modern living.